Extra Dimensions and Kaluza–Klein - Năstase, Horaţiu [UNESP] (My University, 2019)
In this chapter we will study the idea of extra dimensions, as proposed by Kaluza and Klein. The idea of having extra dimensions, besides our usual 3 + 1, is an old one. Already Theodor Kaluza (in 1921) and Oskar Klein (in 1926) had considered it. The general idea of Klein was to consider that our space is a product of our four dimensional space M4 and a small compact space Kn, i.e., KD= M4× Kn, with D= 4 + n. Then if the volume (or rather, the radii) of the extra dimensional space is really small, they would be unobservable. Perhaps the size is comparable to the Planck length lPl, which would be natural in a quantum gravity theory, or maybe otherwise larger, yet still small.